1991
DOI: 10.1007/bf00174745
|View full text |Cite
|
Sign up to set email alerts
|

?Real time? measurement of endogenous dopamine release during short trains of pulses in slices of rat neostriatum and nucleus accumbens : role of autoinhibition

Abstract: Release of endogenous dopamine elicited in slices of rat neostriatum or nucleus accumbens by a single electric pulse or by trains of 4 or 10 pulses was examined using fast cyclic voltammetry. Single electric pulses gave rise to a marked and transient increase in the extracellular concentration of dopamine in the neostriatum (by 0.43 mumol/l) and nucleus accumbens (by 0.39 mumol/l). The overflow elicited by subsequent pulses delivered at a frequency of 0.2 Hz caused separate but much smaller peaks of dopamine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 16 publications
5
68
0
Order By: Relevance
“…Consistent with previous data Bull and Sheehan, 1991;Limberger et al, 1991;Trout and Kruk, 1992;Garris et al, 1994), evoked DA release in C Pu and NAc was regulated strongly by D 2 autoreceptor inhibition, as indicated by the marked enhancement of [DA] o after D 2 receptor antagonism by sulpiride and the reduction of [DA] o during D 2 agonism by quinpirole. The time course of autoinhibition in C Pu was consistent with a time delay for D 2 receptor activation by DA in vitro.…”
Section: Receptor Control Of Axon Terminal Da Releasesupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous data Bull and Sheehan, 1991;Limberger et al, 1991;Trout and Kruk, 1992;Garris et al, 1994), evoked DA release in C Pu and NAc was regulated strongly by D 2 autoreceptor inhibition, as indicated by the marked enhancement of [DA] o after D 2 receptor antagonism by sulpiride and the reduction of [DA] o during D 2 agonism by quinpirole. The time course of autoinhibition in C Pu was consistent with a time delay for D 2 receptor activation by DA in vitro.…”
Section: Receptor Control Of Axon Terminal Da Releasesupporting
confidence: 91%
“…DA was detected with FCV at a carbon fiber microelectrode after electrical stimulation in SNc, VTA, CPu, or nucleus accumbens (NAc), as described previously Palij et al, 1990;Limberger et al, 1991;Trout and Kruk, 1992;Iravani et al, 1996;Cragg et al, 1997;Rice et al, 1997), with either multisecond stimulation trains (30 -40 pulses at 10 Hz) or a pseudo-one pulse stimulation (10 pulses at 100 Hz). The identification of extracellular signals evoked by 10 Hz stimulation as DA and not other monoamines or metabolites was confirmed previously Rice et al, 1997) on the basis of anatomical, electrochemical (see also Figs.…”
Section: Identification Of Da Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Applying a range of anatomical, electrochemical and pharmacological criteria, it has previously been shown that the voltammetric signal, as measured in this study, following electrical stimulation in striatal brain slices can be attributed to a transient increase in extracellular dopamine concentration Bull et al, 1990;Patel et al, 1992;. By use of fast cyclic voltammetry it is possible to measure dopamine overflow evoked by a wide range of electrical stimuli, ranging from a single pulse to long trains applied over a wide range of frequencies with a time resolution which approaches real time Limberger et al, 1991;.…”
Section: Discussionmentioning
confidence: 71%
“…In the neostriatum and nucleus accumbens, dopamine autoinhibition is mediated via dopamine D2-like receptors (Dugast et al, 1997). Although other in vitro studies have demonstrated that activation of release-regulating autoreceptors by short trains of pulses occurs over a time frame of approximately 1 sec (Limberger et al, 1991;Kennedy et al, 1992), the explicit timecourse of action of these autoreceptors on subsequent dopamine release has not been previously determined. Yet the window of such autoinhibition (onset, magnitude, and duration) clearly has important implications for the local control of extracellular dopamine in the forebrain.…”
Section: Discussionmentioning
confidence: 99%